The medical and social answer to requests for euthanasia - Migone, Luigi (Medicina e Morale, 1998)
The urgent bioethical questions that medicine has to deal with the increasing request for the "humanisation" of medicine are the reasons that justify a critical-philosophical revision of medicine in order to redefine its methods, essence, limits and values, through an epistemological analysis. This critical reflection has to make use of philosophical study that "goes beyond mere competence of the single science". Medicine occupies a special place in the field of empirical-experimental sciences, because it is interested in a particular object, the sick man, who can not be considered as just an object. Jaspers mentions that the figure of the physician has to have, "on one hand scientific knowledge and technical ability, and on the other hand, humanitarian ethos". Another point to consider is the physician-patient interpersonal relationship that is to be understood not only as the therapeutic acts but also as a cognitive process of the sick man and his biography, keeping a dialogue open in order to maintain a more humanitarian relationship that takes into consideration the patient's needs. The meeting between medicine and philosophy is born from the need for comprehension and from the conceptualisation omitted by science. In conclusion, the article concentrates on the advantages of a humanisation of medicine aimed to create an ethical reflection that considers another person in his holistic dimension.